Effects of Minor Gadolinium Addition and T4 Heat Treatment on Microstructure and Properties of Magnesium. Issue 12 (9th November 2022) - Lu, Yiyi; Huang, Yuanding; Bode, Julia; Vogt, Carla; Willumeit-Römer, Regine; Kainer, Karl Ulrich; Hort, Norbert
Abstract : Mg–Gd alloys are candidates for degradable implants combining favorable mechanical and corrosion properties. Gd has a high solid solubility in Mg and an acceptable biocompatibility. The influences of different amount of Gd additions and solid solution (T4) treatment on mechanical properties and corrosion in 0.9 wt% NaCl and cell culture medium (CCM) of magnesium are systematically investigated. The effects of Gd are clarified by microstructural characterizations as well as stress and degradation analysis. It is shown that minor Gd additions to pure Mg lead to Gd solid solution in Mg ( α ) and the formation of Mg5 Gd intermetallic particles (IMPs), which increase the hardness, tensile, and compressive strength. The GdH2 phase is found in low‐alloyed Mg–Gd alloys. The corrosion rate (CR) is increased by the addition of more Gd due to the increased kinetics of the cathodic reaction. However, the resistance to degradation is effectively improved by T4 heat treatment due to the dissolution of IMPs. The reduced susceptibility to pitting can be achieved by a minor Gd addition and T4 heat treatment. The Mg–2Gd alloy is a potential candidate for implants due to its good combination of tailorable mechanical properties and low homogeneous in vitro degradation rate (DR). Abstract : Pure Mg and binary Mg– x Gd ( x  = 0.5, 1, 2 wt%) alloys have been prepared through permanent mold casting. Influence of minor Gd addition and T4 heat treatment on microstructure, mechanical, and corrosion properties have been systematically studied. Mg–2Gd alloy is a potential candidate for degradable implants due to its good combination of tailorable mechanical properties and low homogeneous degradation rate.